Socially Responsible Marketing: Toward Aligning Dharma (Duties), Karma (Actions), and Eudaimonia (Well-Being). (December 2022) - Sheth, Jagdish N.; Parvatiyar, Atul
Laczniak and Shultz, in their recent article in the Journal of Macromarketing, provide a robust framework and a comprehensive definition of socially responsible marketing (SRM) anchored on macro-normative ethical perspectives. The explicit purpose of offering this framework and definition is to provide a roadmap to create a better world. Recognizing that marketing has a vital role in enabling the societal goal of achieving well-being and thriving, we offer some additional perspectives in this commentary. Essentially, we suggest how the SRM doctrine can be enriched and enlarged by explicitly aligning societal goals of eudaimonia (well-being) with marketing's moral duties and actions. To do so, we reconcile ethical ideas in Asian and Western philosophies as to how they may help us clarify the requisite SRM behavior. We also look at the developments in evolutionary psychology and developmental biology as to the proper criteria for evaluating the success of SRM behavior.